2005
DOI: 10.1074/jbc.m505249200
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Biochemical Analyses of BACE1- and BACE2-deficient Mice

Abstract: ␤-Secretase (BACE1) is the rate-limiting protease for the generation of the amyloid ␤-peptide (A␤) in Alzheimer disease. Mice in which the bace1 gene is inactivated are reported to be healthy. However, the presence of a homologous gene encoding BACE2 raises the possibility of compensatory mechanisms. Therefore, we have generated bace1, bace2, and double knockout mice. We report here that BACE1 mice display a complex phenotype. A variable but significant number of BACE1 offspring died in the first weeks after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
345
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(377 citation statements)
references
References 42 publications
23
345
2
1
Order By: Relevance
“…Only when mice are backcrossed onto an inbred genetic background (e.g. C57BL/6) do phenotypes become noticeable (21). This suggests that modifier genes in specific genetic backgrounds contribute to BACE1 null phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only when mice are backcrossed onto an inbred genetic background (e.g. C57BL/6) do phenotypes become noticeable (21). This suggests that modifier genes in specific genetic backgrounds contribute to BACE1 null phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports indicated that BACE1 Ϫ/Ϫ mice were viable, fertile, and devoid of abnormalities. However, upon closer examination, BACE1 Ϫ/Ϫ mice were found to have several subtle phenotypes that involved memory deficits (16 -18), hypomyelination (19,20), reduced survival and growth retardation (21), irregularities in neuronal excitability and electrophysiology (17,21,22), seizure (22,23), reduced dendritic spine density (24), schizophrenia endophenotypes (24), and axon guidance defects (1,25). Although these BACE1 null abnormalities are relatively mild, they are complex neurological phenotypes that raise a concern that BACE1 inhibitors may not be completely free of mechanism-based side effects.…”
mentioning
confidence: 99%
“…Subsequent studies on BACE1-deficient mice, however, revealed significant postnatal lethality, reduced body weight, decreased anxiety-related behavior, and hyperactivity. 37 Further investigations found decreased thermal pain threshold, impaired motor coordination, myelination deficits, impaired spatial learning and memory, and altered synaptic function and neurotransmitter metabolism. [38][39][40] As a putative correlate of their learning and memory deficits, Wang et al found that activitydependent potentiation at the mossy-fiber -CA3 synapse in the hippocampus of BACE1-deficient mice is substantially impaired.…”
Section: Bace1-deficient Micementioning
confidence: 98%
“…For example, knock out of the presenilin 1 (PS1) gene, which is a core component of g-secretase complex, resulted in lethality in a mouse model at the embryonic stage (Geling et al, 2002;Shen et al, 1997). On the other hand, b-secretase knock out mice have relatively normal phenotypes and were fully capable of growing up to become normal adults without Ab production (Luo et al, 2001;Roberds et al, 2001), though other studies reported abnormalities in b-secretase knock out mice (Dominguez et al, 2005). Thus, b-secretase is considered a good target for reducing Ab burden in the AD brains.…”
Section: Introductionmentioning
confidence: 99%